Metal Supported SOFCs: Electrochemical Performance under Various Testing Conditions. (30th May 2017) - Haydn, Markus; Bischof, Cornelia; Udomsilp, David; Opitz, Alexander Karl; Bimashofer, Gesara; Schafbauer, Wolfgang; Brandner, Marco; Bram, Martin
Abstract : To demonstrate the performance and reliability of MSCs (Metal Supported SOFCs), a systematic electrochemical characterization on button cells has been performed. The cell conditioning during the first heating-up is described in detail, since there is a significant difference to ESCs (Electrolyte Supported Cell) and ASCs (Anode Supported Cell). The focus of the present work is to show the influence of different anode materials, gas-flow rates, and operation temperatures on recorded i-V-curves. In some cases, fuel utilization rates were used, which are higher than commonly applied in button cell experiments. However, under these harsh conditions, the anode and the metal substrate must handle e.g. high humidity.This paper summarizes recent results on (i) manufacturing, (ii) appropriate test procedures, (iii) electrochemical testing, and (iv) influence of different anode layer materials for MSCs.